Pengaruh Kompensasi, Kesehatan dan Keselamatan Kerja terhadap Kinerja Pegawai Harian Lepas di PT Sarana Inti Transindo Surabaya - Syair De Alam Mantra; Hesty Prima Rini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
To determine whether an organization has a good performance or not, one of the measurement techniques that can be used is to see whether the goals set by the company itself have been achieved or not. PT Sarana Inti Trasindo, a company that offers a wide range of transportation services, mainly focuses on trucks. Especially for casual daily employees who operate in the field of truck drivers, employee performance is still less visible from the problem of late delivery or delivery delays in 2020. The purpose of this study is to look at the K3 elements to see how employee performance and salaries relate to each other. The tool used for data analysis is called Partial Least Square (PLS), and uses this analysis method. Colquitt et al. (2011) defines employee performance as a group of employee behaviors that have a positive or negative effect on the achievement of organizational goals. The health, safety, and welfare of people who work in a facility or project location are the focus of occupational health and safety, often abbreviated as K3, according to Suparno Eko Widodo (2015). Haridoko (2008) claims that "compensation" includes all the benefits that workers get in return for their efforts. Participants in this study were selected from eighty workers from the truck company PT Sarana Inti Trasindo Surabaya. All employees of PT Sarana Inti Trasindo Surabaya who drive trucks are included in the sample of this study. The study findings show that financial compensation and OSH feedback both significantly improve employee performance. It is hoped that PT Sarana Inti Transindo can complete personal protective equipment and also add transportation support equipment to improve the overall performance of personnel. Keywords: Health; Work safety ; Performance ; Compensation